Perbandingan Penggunaan Matlab dan Maple dalam Menentukan Akar Persamaan Menggunakan Metode Bagi Dua - Rejeki, Trimo Bagiono; Lesmana, Anung Candra; Wibowo, Ari (Mandalika Mathematics and Educations Journal, 2025)
Numerical methods play a crucial role in solving non-linear equations that cannot be solved analytically. This study compares the use of two software tools, Matlab and Maple, in determining the roots of non-linear equations using the bisection method. This method iteratively divides the root search interval into two parts until the specified error tolerance is reached. The research employs a descriptive qualitative approach, where two non-linear equations are tested using Matlab and Maple. The analysis results show that both software tools provide nearly identical outputs, with minimal differences due to variations in numerical representation. Matlab excels in numerical programming flexibility and data visualization, while Maple is easier to use as it has built-in functions for the bisection method. The findings of this study are expected to provide insights for users in selecting appropriate software to solve numerical method problems.